Circulating tumour cell clusters: isolation, biological significance and therapeutic implications - Jianglin Zhang; Xin Hong; Qingfeng Chen; Xuefei Liu; Yufan Yang; Guanyin Huang; Jingru Lian; Chunhao Long; Boxi Zhao; Binyu Zhang; Weijian Ye; Junhao Chen; et al. (BMJ Oncology)
Circulating tumour cells (CTCs) and CTC clusters are considered metastatic precursors due to their ability to seed distant metastasis. However, navigating the bloodstream presents a significant challenge for CTCs, as they must endure fluid shear forces and resist detachment-induced anoikis. Consequently, while a large number of cells from the primary tumour may enter the circulation, only a tiny fraction will result in metastasis. Nevertheless, the metastatic potency dramatically increases when CTCs travel in conjunction with other cell types to form CTC clusters, including neutrophils, myeloid-derived suppressor cells, macrophages, platelets, cancer-associated fibroblasts and red blood cells found in circulation. Such heterotypic CTC clustering events have been identified in a variety of cancer types and may serve as intriguing therapeutic targets and novel biomarkers for liquid biopsy. This review summarises recent advances in microfluidic technologies designed for the isolation of CTC clusters and explores the biological properties of distinct types of CTC clusters within the circulatory system. Investigation of the mechanisms of CTC cluster–blood microenvironment interactions may offer a promising avenue for gaining fresh insights into CTC cluster-mediated metastatic progression and reveal potential opportunities for devising personalised antimetastasis treatments.